The Evolution of Marriage and Inheritance Law in Brunei Darussalam: A Comparative and Historical Study - Roziqin, Opik; Fathonih, Ah. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the dynamics and comparisons of Islamic family law in Brunei Darussalam and Indonesia, particularly in terms of codification, regulation, and the adaptation of Shariah principles. Using a qualitative descriptive-analytical method, this research explores the differences between the two countries in marriage registration, divorce rights, guardianship obligations, and the role of mediation in divorce cases. The findings indicate that Brunei applies a centralized Islamic family law system under royal control, while Indonesia adopts a pluralist system that accommodates customary and Shariah laws. The codification in Brunei and the adaptation of Islamic law in Indonesia demonstrate that both countries are able to uphold Shariah principles while adjusting to the needs of modern society. This research emphasizes the importance of balancing traditional values with contemporary legal needs.